The Greener the Better! Avian Communities Across a Neotropical Gradient of Urbanization Density - Escobar-Ibáñez, Juan F.; Rueda-Hernández, Rafael; MacGregor-Fors, Ian (Frontiers in Ecology and Evolution, 2020)
Urbanization has been recognized as one of the most widespread threats to biodiversity. However, the response of wildlife to urbanization differs among groups, with many species being able to persist, adapt, and even thrive in these novel ecosystems. With the aim of assessing the response of avian communities in a neotropical green city, we evaluated their species richness and composition across a gradient of urbanization density comprised by a citywide survey performed in two consecutive years and considering both breeding and non-breeding seasons. As expected, species richness decreased with urbanization. Species loss was drastic when considering data from both years and both seasons, and gradual when seasons were assessed separately. Avian composition for both years and seasons differed largely between the less urbanized and the more urbanized sites, whereas sites with intermediate built cover showed to be more similar to each other. When evaluating avian composition by season in both years, highest differences were recorded between more urbanized sites and all other studied sites, while less urbanized sites showed high similarity regardless of the surveyed season. Sites with intermediate built cover had higher similarity among seasons, showing that such conditions shelter similar species in both seasons. This study presents findings on one of the first citywide gradients of urbanization density from the urban Neotropics, showing both differences and similarities in relation to previous studies from the Global North. Briefly, our species richness results showed a punctuated decrease when considering both seasons and years, rather than a gradual decrease or humped-shaped relations with higher richness at intermediately urbanized sites. Also, our composition findings stress the high representation of insectivore birds as part of avian communities across a citywide gradient of urbanization density. Undoubtedly, identifying the similarities and differences in the urban ecology patterns across cities, together with the particularities of some urban systems, will allow for increased effectiveness of urban management and planning strategies in the transformation toward more livable, resilient, and biodiverse cities.